Do Incumbents' Mergers Influence Entrepreneurial Entry? An Evaluation. (22nd March 2013) - Majumdar, Sumit K.; Moussawi, Rabih; Yaylacicegi, Ulku
<x xml:space="preserve">Abstract</x> This analysis has evaluated the impact of mergers on new entrepreneurial firm entry in the territories of firms making up the local exchange sector of the United States telecommunications industry. An analysis of first and second mergers undertaken by the local exchange companies has revealed that where mergers occurred there was significantly lower entrepreneurial entry. The results have implications for policy, since the approval of mergers has been shown to lead to lower entrepreneurial entry where mergers occur, and the approval of mergers may serve to impede entrepreneurship. Hence, greater thought should be given to merger approvals so that entrepreneurship and the process of economic growth are not compromised as a result.